Sorptive Elimination of Alizarin Red-S Dye from Water Using Citrullus lanatus Peels in Environmentally Benign Way Along with Equilibrium Data Modeling - Rehman, Rabia; Mahmud, Tariq (Asian Journal of Chemistry, 2013)
Textile industry effluents comprised of various toxic and non biodegradable chemicals, especially non-adsorbed dyeing materials, having synthetic origin. Alizarin Red-S dye is one such examples. In this work, sorptive removal of Alizarin Red-S from water was investigated using Citrullus lanatus peels, in batch mode on laboratory scale. It was observed that adsorption of dye on Citrullus lanatus peels increases with increasing contact time and temperature, but decreases with increasing pH. Isothermal modeling indicated that physio-sorption occurred more as compared to chemi-sorption during adsorption of Alizarin Red-S by Citrullus lanatus peels, with qm 79.60 mg g-1. Thermodynamic and kinetic investigations revealed that this process was favourable and endothermic in nature, following pseudo-second order kinetics.